Development with identity [ community, culture and sustainability in the Andes - Rhoades, Robert E. (CABI, 2006)
This book reports on a 6-year interdisciplinary research project on sustainable agriculture and natural resource management in Cotacachi, Ecuador, where scientists and indigenous groups seek common ground. It discusses how local people have engaged the nvironment over time to create contemporary Andean landscapes. Human-environment interaction in relation to biodiversity, soils and water, and equitable development are also discussed. This book is intended for social and biological scientists researching environment and agriculture in rural communities. The book has 21 chapters and a subject index.